Biologic Mechanisms Underlying the Heterogeneous Response to Tight Glycemic Control among Differentially Inflamed Patients in the HALF-PINT Trial - Zinter, Matt S.; Taylor, Clove S.; Markovic, Daniela; Pellegrini, Matteo; Wong, Kayley; Balliu, Brunilda; Gala, Kinisha P.; Asaro, Lisa A.; Nadkarni, Vinay M.; McQuillen, Patrick S.; Vangala, Sitaram S.; Sinha, Pratik; et al. (American journal of respiratory and critical care medicine, 2025)
Tight glycemic control (TGC) with insulin has not consistently shown benefit in critically ill patients. We previously reported that the subset of children with a hyperinflammatory subphenotype benefited from TGC in the HALF-PINT (Heart and Lung Failure - Pediatric Insulin Titration) study of hyperglycemic children with heart and lung failure and the IIT-SBPP (Intensive Insulin Treatment - Severely Burned Pediatric Patients) study in severely burned pediatric patients. However, whether this effect was mediated through a reduction in inflammation or some other biologic process is not fully understood. To deepen the understanding of inflammatory subphenotypes and explore the biologic mechanisms underlying heterogeneous response to TGC. Plasma cytokine measurements and whole-blood transcriptomics from 740 blood samples collected on Pre- and Post-treatment Study Days 0, 2, and 4 from 293 HALF-PINT participants ( = 250 hypoinflammatory and = 43 hyperinflammatory) were used to identify cytokine and gene expression signatures of differential responses to TGC. Patients with the hyperinflammatory subphenotype had greater baseline expression of genes relating to inflammation, cell-cycle activity, and immunometabolism. Hyperinflammatory patients treated to a target glucose range of 80-110 mg/dl experienced greater reductions in inflammatory cytokines, innate immune gene expression, and heme metabolism gene expression, as well as an increase in lymphocyte gene expression, compared with those treated to a target range of 150-180 mg/dl. Causal mediation testing indicated that these changes partly explained the observed mortality benefit of TGC in the hyperinflammatory subgroup of patients. These findings expand our understanding of the biology underlying inflammatory subphenotypes and provide biologic insight into the mortality benefit of TGC in hyperinflammatory children.